Students' Perception of the Effectiveness of Using Duolingo Application as a Foreign Language Learning Platform - Benny Putra; Syamsu T; Nurul Faradillah; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to explore students' perceptions of the effectiveness of using Duolingo as a foreign language learning platform for first semester English education students. The researcher identified the extent to which Duolingo app is effective in assisting foreign language learning and evaluated how effective the app is in assisting students in foreign language learning. A descriptive qualitative approach was used, and data were collected through observation, questionnaires, and interviews with second-semester students of the English Education Study Program at Universitas Muhammadiyah Sidenreng Rappang. The findings show that most students have a positive perception of Duolingo. They found the app easy to use, interesting, and helpful in understanding and memorizing vocabulary. Features such as repetition, daily reminders, and interactive design were found to increase learning motivation and student engagement. However, Duolingo's effectiveness in a structured classroom setting was considered neutral due to limitations in its integration into formal teaching methods. Overall, Duolingo is considered an effective tool for self-directed English vocabulary learning.